Pengolahan Hasil Pertanian Jagung untuk Meningkatkan Perekonomian Desa - Asifha Defitrian Salsabila; Solfema Solfema; Lili Dasa Putri (Lembaga Pengembangan Kinerja Dosen, 2025)
Corn is one of the main food commodities in Indonesia which plays an important role in meeting food needs and supporting the economy. Empowering corn farmers is an effort made to increase the capacity and independence of farmers in increasing productivity and quality of harvest results. Empowerment programs that can be provided to corn farmers are training, increasing access to technology, financial support and strengthening the market for corn farmers.